A long-term study of the magnetic field and activity in the M giant RZ Ari - Konstantinova-Antova, R.; Georgiev, S.; Lèbre, A.; Palacios, A.; Morin, Julien; Bogdanovski, R.; Abbott, C.; Baron, F.; Aurière, M.; Drake, N, A; Tsvetkova, S.; Josselin, E.; et al. (Astronomy & Astrophysics, 2024)
International audience Aims. We present a detailed long-term study of the single M6 III giant RZ Ari to obtain direct and simultaneous measurements of the magnetic field, activity indicators, and radial velocity in order to infer the origin of its activity. We study its magnetic activity in the context of stellar evolution, and for this purpose, we also refined its evolutionary status and Li abundance. In general, for the M giants, little is known about the properties of the magnetic activity and its causes. RZ Ari possess the strongest surface magnetic field of the known Zeeman-detected M giants and is bright enough to allow a deep study of its surface magnetic structure. The results are expected to shed light on the activity mechanism in these stars. Methods. We used the spectropolarimeter Narval at the Télescope Bernard Lyot (Observatoire du Pic du Midi, France) to obtain a series of Stokes I and Stokes V profiles for RZ Ari. Using the least-squares deconvolution technique, we were able to detect the Zeeman signature of the magnetic field. We measured its longitudinal component by means of the averaged Stokes V and Stokes I profiles. In addition, we also applied Zeeman-Doppler imaging (ZDI) to search for the rotation period of the star, and we constructed a tentative magnetic map. It is the first magnetic map for a star that evolved at the tip of red giant branch (RGB) or even on the asymptotic giant branch (AGB). The spectra also allowed us to monitor chromospheric emission lines, which are well-known indicators of stellar magnetic activity. From the observations obtained between September 2010 and August 2019, we studied the variability of the magnetic field of RZ Ari. We also redetermined the initial mass and evolutionary status of this star based on current stellar evolutionary tracks and on the angular diameter measured from CHARA interferometry. Results. Our results point to an initial mass of 1.5 M ⊙ so that this giant is more likely an early-AGB star, but a lotaction at the tip of the RGB is not ...